Development and evaluation of the Dutch Healthy Diet index 2015. Issue 13 (19th June 2017) - Looman, Moniek; Feskens, Edith JM; de Rijk, Mariëlle; Meijboom, Saskia; Biesbroek, Sander; Temme, Elisabeth HM; de Vries, Jeanne; Geelen, Anouk
Abstract: Objective: To update the Dutch Healthy Diet index, a measure of diet quality, to reflect adherence to the Dutch dietary guidelines 2015 and to evaluate against participants' characteristics and nutrient intakes with the score based on 24 h recall (24 hR) data and FFQ data. Design: The Dutch Healthy Diet index 2015 (DHD15-index) consists of fifteen components representing the fifteen food-based Dutch dietary guidelines of 2015. Per component the score ranges between 0 and 10, resulting in a total score between 0 (no adherence) and 150 (complete adherence). Setting: Wageningen area, the Netherlands, 2011–2013. Subjects: Data of 885 men and women, aged 20–70 years, participating in the longitudinal NQplus study, who filled out two 24 hR and one FFQ, were used. Results: Mean (sd ) score of the DHD15-index was 68·7 (16·1) for men and 79·4 (16·0) for women. Significant inverse trends were found between the DHD15-index and BMI, smoking, and intakes of energy, total fat and saturated fat. Positive trends were seen across sex-specific quintiles of the DHD15-index score with energy-adjusted micronutrient intakes. Mean DHD15-index score of the FFQ data was 15·5 points higher compared with 24 hR data, with a correlation coefficient of 0·56 between the scores. Observed trends of the DHD15-index based on FFQ with participant characteristics, macronutrient and energy-adjusted micronutrient intakes were similar to those with the DHD15-index based on 24 hR. Conclusions: The DHD15-index score assesses adherence to the Dutch dietary guidelines 2015 and indicates diet quality. The DHD15-index score can be based on 24 hR data and on FFQ data.